Javanese Language Registers in Ling Ling Lieanti’s Content: A Sociolinguistic Study - Ika Nurhidayah; Prembayun Miji Lestari; Nur Fateah (Universitas Negeri Semarang, 2026)
The rapid development of digital media has encouraged the emergence of content creators who utilize language variation as a communication strategy, including the uses of regional languages. This study aims to describe the forms and meanings of Javanese language registers used in the digital content of Ling Ling Lieanti, a content creator from Semarang known for her distintive Semarangan Chinese-Javanese accent. This research employed a descriptive qualitative method with a sociolinguistic approach. The data consisted of utterances containing Javanese registers obtained from Ling Ling Lieanti's content uploaded on YouTube, Instagram, and TikTok from June 2024 to May 2025. Data were collected through observation, listening, transcription, and note taking techniques, then analyzed using pragmatic and referential equivalent methods including data transcription, identification of lingual units, data classification, analysis of scope of use, and drawing conclusions. The results show that the Javanese registers in Ling Ling Lieanti's content are categorized into linguistics forms consisting of single word forms and complex forms, including affixation, reduplication, compounding, and abbreviation. In terms of usage scope, the registers are divided into restricted and open registers. Furthermore, the meanings identified include lexical, contextual, social, and cultural meanings. The study demonstrates that Javanese language registers function not only as communication tools but also as markers of local identity, humor, social relationship, and cultural representation in digital media.